Where the light falls : selected stories of Nancy Hale - Hale, Nancy, 1908-1988 (Library of America, 2019)
A teenage girl in Connecticut driven to near delirium over her burgeoning sexuality. A twenty-something New Yorker transplanted to a small Virginia community who boldly befriends the town pariah. A New England widow in search of alcohol and excitement while babysitting her grandson. A Maryland socialite who has built a secret bomb shelter that becomes the center of her imaginative life. These are some of the characters who inhabit Nancy Hale<U+2019>s lush fiction. Haunting, vivid, and wonderfully subversive, Hale<U+2019>s stories typically concern women recognizable to all of us<U+2014>sometimes fragile, possibly wicked, deceptively ordinary, navigating their way uncertainly through life. Nancy Hale was one of the most accomplished short story artists of her era, winner of ten O. Henry Awards and a frequent contributor to The New Yorker from the 1930s to the 1960s. But by the time of her death in 1988, this remarkable writer, so far ahead of her time in her depiction of complex women, was largely forgotten. Now Lauren Groff reintroduces this modern master with a selection of twenty-five of her best stories<U+2014> brilliant short fiction that encompasses childhood and adolescence, marriage and motherhood, desire and infidelity, madness and memory.